Humanizing STEM education: an exploratory study of faculty approaches to course redesign - Azizi, Mehri; Imad, Mays; Foote, Stephanie M.; Caulkins, Joshua; Wuetherick, Brad (Frontiers in Education, 2023)
This study presents the findings from the analysis of reflections from 26 STEM faculty at various institutions of higher education across the United States who participated in the online course, The Humanity of Inclusive Practices, part of the Teaching and Learning Academy, offered by the John N. Gardner Institute (Gardner Institute) for Excellence in Undergraduate Education. Participants answered three questions at the end of the online course: what are your equity challenges? What are your goals? Humanizing STEM Education 2How do you measure your success?; we analyzed responses using grounded theory. Findings from this study suggest that student-teacher positionality and inequity in prior knowledge may cause equity challenges for educators. Furthermore, the findings suggest that participants in the course set goals such as increasing student success (grades) in the course, empowering students, and incorporating inclusive material in curricula to humanize their course(s). Lastly, the findings reveal that educators measure their success through grades, as well as student engagement and feedback. Recommendations on how to tackle the challenges associated with humanizing STEM course redesign are provided.